"Singgappenne": Women's Sports in Tamil Cinema. Issue 1 (10th March 2022) - Karupiah, Premalatha
Abstract: Women's sports drama is a new addition to the increasing number of genres in post‐millennial Tamil cinema. This article analyzes the representation of women's empowerment through sports in two such Tamil films: Bigil (Atlee 2019) and Kanaa (Kamaraj 2018). Bigil is a hero‐centric football movie while Kanaa is a heroine‐centric cricket movie. Qualitative content analysis was used to explore the representation of women athletes in both movies. Both movies show the various challenges women athletes face in pursuing their dreams. However, Kanaa is a more realistic portrayal of women's sports and gives much more voice to the female protagonist when compared to Bigil . In Bigil, the coach is presented as a savior who helps women athletes excel in football. In Kanaa, the coach plays a realistic role of defending, supporting, and training his players to succeed.